Political economy of monetary union in Europe. - DE GRAUWE, Paul (1993)
Analyses the reasons why the Maastricht Treaty is unlikely to lead to monetary union before the end of the decade. Concludes that the transition process described in the Maastricht Treaty was devised for political reasons, and there is no economic case for stretching the transition to monetary union.